Assessing the effectiveness of indigenous phosphate-solubilizing bacteria in mitigating phosphorus fixation in acid soils - Sen, Arup; Saha, Niharendu; Sarkar, Arindam; Poddar, Ratneswar; Pramanik, Krishnendu; Samanta, Anwesha (3 Biotech, 2024)
Phosphorus (P) is the key to several structural molecules and catalyzes numerous biochemical reactions in plant body besides its involvement in energy transfer. Any deficit in P availability is likely to result in reduced RNA and protein content, inhibiting crop growth and development. Thus, availability of soil P is extremely crucial for plant growth especially in acid soils of India, where most of the fraction is bound to solid phase rendering their availability. The present communication deals with the isolation of elite phosphate-solubilizing bacterial (PSB) strains from the acid soils to work out their ability to improve the fertilizer P use efficiency in the acidic environment. Initially twenty-six bacteria were isolated from the acid soils of Northeastern India. Among them, ten bacteria were selected based on formation of halo zone in the Pikovskaya agar plate. In addition, these bacteria were able to solubilize insoluble zinc (Zn) and potassium (K). The isolates were subject to in vitro optimization for P solubilization under different insoluble P source utilization and at different pH and salinity conditions. Strains AN3, AN11, and AN21 exhibited significant solubilization of insoluble P, Zn, and K, and were identified as Streptomyces sp., Enterobacter sp., and Paraburkholderia caribensis . These three bacteria solubilized 206.53 to 254.08 µg mL −1 P, 79.7 to 177.55 µg mL −1 Zn, and 0.96 to 1.56 µg mL −1 K from insoluble minerals. Their performance was further evaluated in pot culture experiment using green gram as test crop. These three bacteria were found to improve P uptake and dry matter accumulation in green gram plant substantially. Seed bio-priming with the PSB strains enhanced the efficiency of added P fertilizer, resulting in a 1.40 to 1.52 times higher effectiveness compared to the control. On the whole, AN11 may be ranked as best inoculant for the acidic soils of Northeastern India.